A High Incidence of Perineal Post-Related Complications After Hip Arthroscopy Is Self-Reported by Patients in Anonymous Online Forums - Brendan M. Holderread, M.D; Austin E. Wininger, M.D; Justin Cho, B.S; Deven Patel, B.S; Anthony Echo, M.D; R. Chad Mather, M.D; Matthew J. Kraeutler, M.D; Joshua D. Harris, M.D (Elsevier, 2024)
Purpose: To evaluate online, self-reported pudendal nerve or perineal injuries related to the use of a perineal post during hip arthroscopy. Methods: Public posts on Reddit and the Health Organization for Pudendal Education were searched to identify anonymous individuals reporting symptoms of pudendal nerve or perineal injury following hip arthroscopy. Included posts were by any individual with a self-reported history of hip arthroscopy who developed symptoms of pudendal nerve injury or damage to the perineal soft tissues. Demographic information and details about a person's symptoms and concerns were collected from each post. Descriptive statistics were used to analyze the data. Results: Twenty-three online posts reported on a perineal post-related complication following hip arthroscopy. Sex information was available in 16 (70%) posts (8 male, 8 female). Twenty-two posts reported a sensory injury, and 4 posts reported a motor injury with sexual consequences (sexual dysfunction, dyspareunia, impotence). Symptom duration was available in 15 (65%) posts (8 temporary, 7 permanent). Permanent symptoms included paresthesia of the perineum or genitals (7) and sexual complaints (5). Two posts stated they were counseled preoperatively about the possibility of this injury. Zero patients reported that a postless hip arthroscopy alternative was an option made available to them before surgery. Conclusions: A high incidence of permanent pudendal nerve, perineal skin, and genitourinary/sexual complications are self-reported and discussed online by patients who have undergone post-assisted hip arthroscopy. These patients report being uninformed and undereducated about the possibility of sustaining a post-related complication. No patient reported being informed of postless hip arthroscopy preoperatively. Clinical Relevance: Identifying and evaluating self-reported patient information in online medical forums can provide important information about patient experiences and outcomes.